2011
DOI: 10.1539/joh.l10037
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Cognitive‐behavioral Stress Management Program for Secondary School Teachers

Abstract: This study aimed to assess the efficacy of a brief cognitivebehavioral program that was designed to reduce the work-related stress levels of secondary school teachers. Methods: A quasi-experimental design was used to compare the intervention groups with the wait-list control groups. Seventy teachers from the intervention groups and 54 from the control groups completed a set of validated scales at the baseline and 3-4 wk later. The scales included the Depression Anxiety Stress Scale, the Dysfunctional Attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 26 publications
3
39
0
2
Order By: Relevance
“…Online stress management programs are effective if participants enjoy these, and have been shown to be more easily accessible and more cost-effective than traditional programs 2325. Cognitive-behavioral stress management programs have been shown to be effective in reducing dysfunctional thought and decreasing stress 26,27. These general observations regarding stress management programs could be used to design programs specifically for dental students.…”
Section: Discussionmentioning
confidence: 96%
“…Online stress management programs are effective if participants enjoy these, and have been shown to be more easily accessible and more cost-effective than traditional programs 2325. Cognitive-behavioral stress management programs have been shown to be effective in reducing dysfunctional thought and decreasing stress 26,27. These general observations regarding stress management programs could be used to design programs specifically for dental students.…”
Section: Discussionmentioning
confidence: 96%
“…Traditional cognitive‐behavioral approaches focus on specific, manual‐based treatment protocols (e.g., acceptance and commitment therapy [ACT] Hayes, ; Vujanovic et al, ). Interventions of this type include ACT (Jeffcoat & Hayes, ), and the use of a cognitive‐behavioral stress management curriculum (Shimazu, Okada, Sakamoto, & Miura, ; Zolnierczyk‐Zreda, ; Leung, Chiang, Mak, & Wong, ). Cognitive‐behavioral stress interventions are feasible for workplace wellness programs, and they promote general health and well‐being for employees (Riley et al, ).…”
Section: Cognitive‐behavioral Interventionsmentioning
confidence: 99%
“…CBSM comprised of in-session exercise and homework to apply these techniques to personal life experiences. Researchers have been demonstrated that CBSM is associated with improvement of health-related outcomes and reduced perceived stress and stress-related physiological responses in patients with cancer,107,108 human immunodeficiency virus infection,109 and chronic fatigue syndrome,110 as well as healthy subjects 111,112…”
Section: Interventionsmentioning
confidence: 99%